Implementing Quizizz Paper as an Assessment Tool in Islamic Jurisprudence Learning - Ikna, Ikna Ia Naturrohmah; Endi Suhendi (Yayasan Sahabat Literasi Edukasi dan Publikasi Bandung, 2025)
This study aims to examine the planning, implementation, and outcomes of using Quizizz Paper Mode as an assessment medium in Islamic Jurisprudence learning for Grade IX students at MTs Negeri 2 Kota Bandung. The study employed a descriptive qualitative approach involving the Islamic Jurisprudence teacher and Grade IX students as research participants. Primary data were collected through in-depth interviews and passive participant observation, while secondary data were obtained from relevant documentation. Data analysis was conducted interactively through data collection, reduction, display, and conclusion drawing. The findings indicate that the implementation of Quizizz Paper Mode was supported by thorough planning, including the preparation of learning tools, assessment items, technical media, and trial testing. The implementation involved distributing QR cards to students, displaying questions, and allowing students to respond by showing the QR cards. The results demonstrate increased student enthusiasm and engagement in assessment activities, as well as improved efficiency for teachers, particularly in grading processes. Despite challenges such as the potential for cheating and dependence on technological devices, Quizizz Paper Mode proved to be an effective and efficient assessment medium.